Introducing an oncoplastic approach for centrally located breast cancer patients - Mohammadreza Karoobi; Seyed Mostafa Meshkati Yazd; Fatemeh Aminolroaya; Hadiseh Mahram; Samineh Saghafinia; Stefano Pompei; Nahid Nafissi; Pantea Khalili (World Journal of Surgical Oncology)
Abstract Introduction Central breast cancers pose a unique challenge to oncoplastic surgeons, given their proximity to the nipple-areola complex and the impact on cosmetic outcomes. This study aims to present a comprehensive algorithm designed to optimize surgical planning and enhance aesthetic outcomes for patients undergoing surgery for central breast cancers. Methods and materials This cohort study presents an algorithm designed to guide surgical decision-making for patients with central breast cancer and assesses outcomes based on its comprehensive application. Aesthetic outcomes were assessed using the Harvard Scale for physician-reported evaluation, while a modified version of the BREAST-Q questionnaire was systematically used for patient-reported aesthetic assessment. Results Among 53 cases, the Harvard score was 4 in 21%, 3 in 77%, and 2 in 2% of patients. Breast-Q results revealed high satisfaction levels: 67% were “very satisfied” with their breasts, 75% “completely agreed” with satisfaction regarding the outcome, and 81% were “somewhat satisfied” with their nipples. Bland-Altman analysis presented minimal disagreement between Harvard scores and Breast-Q components, with a trend toward correlation observed (rho = 0.251, P = 0.072). Conclusion Advanced oncoplastic techniques, including reduction mammoplasty and mastopexy, offer flexible options for managing central cancers involving the NAC. Use of a nearby skin island for NAC replacement allows tailored approaches beyond the Grisotti flap, ensuring oncologic safety and improved aesthetic outcomes.